Respuesta :

Answer:

a) x = 12

b) y = -2

c) a = 3

d) x = -1/24

e) x = -21

Step-by-step explanation:

[tex]a) \ \dfrac{5 \cdot x}{6} =10[/tex]

Multiply both sides by 6

[tex]\therefore \dfrac{5 \cdot x}{6} \times 6 =10 \times 6[/tex]

6/6 = 1

∴ 5·x × 1 = 10 × 6 = 60

x = 60/5 = 12

x = 12

b) -8.3·y - 2.3 = 14.3

Add 2.3 to both sides

-8.3·y + (- 2.3 + 2.3) = 14.3 + 2.3

-8.3·y + 0 = 16.6

Divide both sides by (-8.3)

-8.3·y/(-8.3) = 16.6/(-8.3)

-8.3·y/(-8.3) = y·(-8.3)/(-8.3) = y × 1 = y = 16.6/(-8.3) = -2

∴ y = -2

c) 7·a - 1 = a + 17

Subtract 'a' from both sides gives;

7·a - 1 - a = a + 17 - a

7·a - 1 - a = a + 17 - a = a - a + 17 = 17

7·a - 1 - a = 7·a - a - 1 = 6·a - 1 = 17

Add 1 to both sides gives;

6·a - 1 + 1 = 17 + 1 = 18

6·a - 1 + 1 = 6·a + 0 = 18

6·a = 18

a = 18/6 = 3

∴ a = 3

d) -6·x = (1/4)

Divide both sides by (-6) gives;

-6·x/(-6) = (1/4)/(-6) = 1/(4 × (-6)) = -1/24

∴ x = -1/24

e) 6·x + 2 = -19 + 5·x

Subtract 5·x + 2 from both sides gives;

6·x + 2 - (5·x + 2) = -19 + 5·x - (5·x + 2)

6·x - 5·x + 2 - 2= -19 - 2 + 5·x - 5·x

x = -21.